ZDHHC7-mediated S-palmitoylation of ATG16L1 facilitates LC3 lipidation and autophagosome formation - Wei, Fujing; Wang, Yu; Yao, Jia; Mei, Ligang; Huang, Xue; Kong, Hesheng; Chen, Jing; Chen, Xiaorong; Liu, Lu; Wang, Zhuolin; Wang, Jiaxin; Song, Jiong; et al. (Autophagy, 2024)
Macroautophagy/autophagy is a fundamental cellular catabolic process that delivers cytoplasmic components into double-membrane vesicles called autophagosomes, which then fuse with lysosomes and their contents are degraded. Autophagy recycles cytoplasmic components, including misfolded proteins, dysfunctional organelles and even microbial invaders, thereby playing an essential role in development, immunity and cell death. Autophagosome formation is the main step in autophagy, which is governed by a set of ATG (autophagy related) proteins. ATG16L1 interacts with ATG12-ATG5 conjugate to form an ATG12-ATG5-ATG16L1 complex. The complex acts as a ubiquitin-like E3 ligase that catalyzes the lipidation of MAP1LC3/LC3 (microtubule associated protein 1 light chain 3), which is crucial for autophagosome formation. In the present study, we found that ATG16L1 was subject to S-palmitoylation on cysteine 153, which was catalyzed by ZDHHC7 (zinc finger DHHC-type palmitoyltransferase 7). We observed that re-expressing ATG16L1 but not the S-palmitoylation-deficient mutant ATG16L1 C153S rescued a defect in the lipidation of LC3 and the formation of autophagosomes in ATG16L1-KO (knockout) HeLa cells. Furthermore, increasing ATG16L1 S-palmitoylation by ZDHHC7 expression promoted the production of LC3-II, whereas reducing ATG16L1 S-palmitoylation by ZDHHC7 deletion inhibited the LC3 lipidation process and autophagosome formation. Mechanistically, the addition of a hydrophobic 16-carbon palmitoyl group on Cys153 residue of ATG16L1 enhances the formation of ATG16L1-WIPI2B complex and ATG16L1-RAB33B complex on phagophore, thereby facilitating the LC3 lipidation process and autophagosome formation. In conclusion, S-palmitoylation of ATG16L1 is essential for the lipidation process of LC3 and the formation of autophagosomes. Our research uncovers a new regulatory mechanism of ATG16L1 function in autophagy. Abbreviation: ABE: acyl-biotin exchange; ATG: autophagy related; Baf-A1: bafilomycin A 1 ; 2-BP: 2-bromopalmitate; CCD: coiled-coil domain; co-IP: co-immunoprecipitation; CQ: chloroquine; EBSS: Earle's balanced salt solution; HAM: hydroxylamine; KO: knockout; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; NP-40: Nonidet P-40; PBS: phosphate-buffered saline; PE: phosphatidylethanolamine; PtdIns3K-C1: class III phosphatidylinositol 3-kinase complex I; PTM: post-translational modification; RAB33B: RAB33B, member RAS oncogene family; RB1CC1/FIP200: RB1 inducible coiled-coil 1; SDS: sodium dodecyl sulfate; SQSTM1/p62: sequestosome 1; TEM: transmission electron microscope; WD: tryptophan and aspartic acid; WIPI2B: WD repeat domain, phosphoinositide interacting 2B; WT: wild-type; ZDHHC: zinc finger DHHC-type palmitoyltransferase.